Policy analysis of self-care program: a qualitative study protocol - Mohammadjavad Mohammadzade; Mostafa Amini-Rarani; Fereshteh Zamani-Alavijeh; Saeed Karimi (Health Research Policy and Systems)
Abstract Background Over the recent years, the self-care program has been a significant policy in the field of health. The WHO recommended self-care for every country and economic setting for reaching universal health coverage, promoting health, keeping the world safe and serving the vulnerable. Conducting a policy analysis study can be useful in closely examining the self-care program’s content, process, context and actors. Methods A qualitative policy analysis will be conducted in four phases to analyse the self-care program, focussing in Iran. The first phase will involve a scoping review to identify policies related to self-care worldwide. In the second phase, a qualitative study will be conducted to determine the status of the self-care program in Iran. The third phase will involve analysing the self-care program in Iran using the policy triangle framework of Walt and Gilson (1994). In the final phase, initial policy recommendations related to the self-care program will be formulated, and validation and finalization of the initial recommendations will be carried out in a panel of experts. Discussion To thoroughly examine the self-care program’s content, process, context and actors, a policy analysis study can be helpful. Therefore, this study will aim to analyse the self-care program using policy analysis approach. By identifying the challenges of the program’s content, process, context and actors, corrective solutions to improve the program’s current status, as well as policy recommendations appropriate to the country’s context, will be provided. In addition, policy-makers in various authorities at the national, regional and provincial levels would benefit from the results of this study.